Efektivitas Pemberian Pisang Ambon (Musa Acuminata Cavendish) dan Pepaya (Carica Papaya Linn) Terhadap Peningkatan Kadar Haemoglobin Ibu Hamil - Rosmaria Rosmaria; Ruwayda Ruwayda; Erni Angraini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Anemia in pregnancy is the condition of the mother with hemoglobin levels below 11 g% in I and III trimester or levels <10,5 gr % in the II trimester. The number of pregnant women with anemia in the Province of Jambi as much as 11.5%, or 8.019 people while the prevalence of anemia in Muaro Jambi by 4.9% or 359 pregnant women. The impact of anemia in pregnancy for the mother can cause abortion, preterm labor, bleeding, while the impact of anemia in the fetus can be the occurrence of abortion, low birth weight and the level of intelegence the baby is low. This research aims to know the description of the levels of Hb pregnant women before and after the Banana and Papaya. This research is experimental method with Pre-Experimental Design and draft of the two group pre-test post-test design. The sample in this research is taken by accidental sampling as many as 25 people to the experimental group with Banana and 25 people to the experimental group with Papaya. Processing and analysis of data test using statistic Paired Simple T-test. The results of the analysis obtained a significant value of p (0,000) < α (0.05), which means the granting of Banana and Papaya has a significant influence on the increase in hemoglobin levels of pregnant women with anemia in the Puskesmas Tangkit Muaro Jambi. Banana and Papaya effect on the increase in hemoglobin levels of pregnant women with anemia. Expected to researchers can further develop this research further about how non-pharmacological in reducing the incidence of anemia with the other things that can be studied and discussed in the research